Smart cooling pad system - Muhammad Ridzuan, Mohd Johari (2019)
Todays, the use of laptops is often used by students and office workers. This is because they need to complete all assigned work. Frequent use of laptops can cause high heat generation by laptops. This can cause their laptop to break down quickly. This can be more dangerous if they rarely clean the cooling system inside their laptop. With the help of an extra cooling system such as a cooling pad, the heat rate accumulated on the laptop can be reduced. Therefore, the idea of developing a cooling pad system has been presented in this project. The objective of this system is to facilitate the use of cooling pads with the control of mobile applications. This system also saves electricity as it works with automated systems. By using this mobile application system, users can remotely control this cooling pad system when receiving a warning message. This can help when a consumer's laptop is hot when it is left off.